Switched reluctance motor: Research trends and overview - Jin-Woo Ahn; Grace Firsta Lukman (CES Transactions on Electrical Machines and Systems, 2018)
There has been a growing interest in switched reluctance motor (SRM) ever since the development of thyristor in 1956. The most appealing feature of SRM which attracts researchers over these years is its simple structure that incorporates concentrated windings on the stator poles and plain laminations of ferromagnetic material as a rotor. Due to this attributes, advances are being made rapidly with the consideration that SRM can be used as an alternative to DC motors and permanent magnet motors. The objective of this paper is to present an overview of the recent developments and a prediction of possible future advancements in SR Drives. Brief history, importance, innovations in structure and control, along with practical application examples are all discussed here to give a more in-depth comprehension of the motor.